The Teacher’s Perception on Learning Media Based on Local Resources in Kindergarten in Pontianak City - Desni Yuniarni (JETL (Journal of Education, Teaching and Learning), 2019)
The learning media has an important role in a learning activity, especially for early childhood education. Media in learning functions to facilitate the student in a learning activity. Through the media, it will be easier for children to comprehend the material as well as making learning activity becomes more fun. Besides, the using of media in learning will stimulate all the children's development aspect. The Pontianak city itself has many local resources that can be used as learning media in kindergarten. The using of local resources as a learning media, in addition to low cost has many benefits, i.e. introducing the various local resources around the children. By getting to know about those resources, it is hoped that the children will be proud and love their city more. But, the phenomenon in kindergarten is teachers prefer the factory-made learning media even though many more benefits for both teachers and children for using the media from their local resources. Thus, the study aims to find out about the teacher's perception toward learning media that based on local resources in kindergarten in Pontianak city. This is a quantitative descriptive study in a survey form. The sampling method used was purposive sampling. The data was obtained using a questionnaire and interview. Data were then analyzed using quantitative descriptive percentage analysis. The study finding shows that 75% of kindergarten teachers in Pontianak city agreed that the using of learning media that based on local resources, it is important for early childhood development; total 36% teachers agreed on the benefits that the students get in using the learning media that based on local resources, while 45% of teachers did not really agree with using that media in learning activities in kindergarten.